A Study Analyzing the Association between Post-Traumatic Embitterment Disorder and Workplace Bullying - KARATUNA, IŞIL; GÖK, SİBEL (Routledge, 2014)
The aim of this study was to investigate the association between perceived victimization from workplace bullying and self-reported embitterment reactions. Data were obtained through anonymous questionnaires from 397 participants working in the public sector. Among the participants, 23.9% were labeled as victims of bullying. Significant differences were observed in the mean scores of post-traumatic embitterment disorder between victims and nonvictims and experiencing bullying was found to be highly in correlation with displaying embitterment reactions. Feelings of injustice, intrusive thoughts, and negative mood were determined as the reactions that received the highest mean scores among victims. © 2014 Copyright Taylor & Francis Group, LLC.
Keywords: mobbing; post-traumatic embitterment disorder (PTED); psychological health; victimization; workplace bullying